2018
DOI: 10.1111/1759-7714.12639
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary meningioma presenting as a micro solid nodule: A rare case report

Abstract: An ectopic meningioma, such as a primary pulmonary meningioma (PPM), is a rare type of tumor that primarily originates outside of the central nervous system. A 65‐year‐old female patient underwent a thoracoscopic lung wedge resection of the right lower lobe for a micro solid nodule detected via computed tomography. The histologic result revealed a PPM. PPMs manifested with micro solid nodules are a very rare occurrence in clinical practice. Increased awareness of the clinical and pathological characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…While a few malignant cases have been documented as relapsing despite receiving treatment [10], most nodules are benign, well-circumscribed, and solitary; consequently, surgical intervention through wedge resection or lobectomy are the main treatment modalities. Sub-centimeter micronodules have also been diagnosed as PPM [12]; however, they are surgically difficult to resect.…”
Section: Discussionmentioning
confidence: 99%
“…While a few malignant cases have been documented as relapsing despite receiving treatment [10], most nodules are benign, well-circumscribed, and solitary; consequently, surgical intervention through wedge resection or lobectomy are the main treatment modalities. Sub-centimeter micronodules have also been diagnosed as PPM [12]; however, they are surgically difficult to resect.…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas are relatively common tumors of the central nervous system. The incidence of an ectopic meningioma is 1%–2% of meningiomas, and the lungs are an uncommon site 1 . Primary pulmonary meningiomas (PPM) often occur in middle‐aged or older individuals, with a slight predominance in women.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of an ectopic meningioma is 1%-2% of meningiomas, and the lungs are an uncommon site. 1 Primary pulmonary meningiomas (PPM) often occur in middle-aged or older individuals, with a slight predominance in women. Weiss et al reported the first case of PPM, identifying it as a rare, slow-growing tumor.…”
Section: Discussionmentioning
confidence: 99%
“…However, malignant PPM may develop distant metastasis or postoperative recurrence. [20] Currently, PPM is thought to have 2 histological origins, such as subpleural multipotential stromal cells and ectopic arachnoid cells. [5] Many pathological differential diagnoses need to be considered for PPM, including sarcomatoid mesothelioma, spindle cell thymoma, spindle cell carcinoma, solitary fibrous tumor, inflammatory myofibroblastic tumor, epithelioid hemangioendothelioma, synovial sarcoma, as well as metastatic tumor.…”
Section: Discussionmentioning
confidence: 99%